Efektivitas Model Scramble untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa SD - Tua Halomoan Harahap; Arief Aulia Rahman (Journal on Education, 2022)
The formulation of the problem in this research is whether the application of Scramble learning model can improve mathematics learning outcomes in students of class V SDS attaufiq. Subjects in this study were students consisting of 38 students. The objects of this research is the application of scramble learning model. Preliminary data and test of students learning completeness are written in the form of tables and pictures. In the initial test students learning completeness level is classically obtained by 3 students (7,89%) completed and 35 students (92,11%) which is not complete. In the first cycle increased to 15 students (39,47%)complete, in the second cycle increased to 34 students (81,58%) thoroughly. The results of classroom observation increased from the first cycle to an average of 1,63 with good category, and the second cycle obtained an average of 2,75 with good category. This is students successfully reviewed from the mastery of student learning. Based on the data obtained then got the conclusion that the learning model scramble can improve student learning outcomes on the subject mathematics plane figure